PEMILIHAN DESA TERBAIK DI KECAMATAN PAGAR MERBAU MENGGUNAKAN METODE AHP - Anita Sindar RMS (JSAI (Journal Scientific and Applied Informatics), 2018)
The empowerment of rural communities needs to be done institutional strengthening, increased motivation and self-help in community cooperation, so that in order to assess the success of village development, it is necessary to conduct a targeted, coordinated, integrated and sustainable assessment. with an assessment indicator. Village assessment is best done by comparing the latest development level based on village profile data in accordance with the assessment indicators. This study aims to build a decision support system to determine the best village based on the village assessment score using the Analytic Hierarchy Process (AHP) method. Basically, the decision-making process is to choose an alternative. The best village assessment consists of 6 criteria. The output of this system is the ranking of each village that has been assessed so as to produce recommendations for decision making in determining the best village. The highest total value of each row calculated by each sub-criteria is summed, the highest total value used is the basis for ranking the best village, Desa Pasar Miring with a final value = 0.969.